Intensity of Audiovisual Media Use and Student Interest in Learning Islamic Religious Education - Aura Mahdiyyah; Alfian Tanjung (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2026)
Abstrak Penelitian ini dilatarbelakangi oleh masih rendahnya minat siswa dalam belajar Pendidikan Islam, meskipun fasilitas media pembelajaran, termasuk media audio-visual, semakin lengkap di sekolah. Penelitian ini bertujuan untuk mengetahui hubungan antara intensitas penggunaan media audio-visual dengan minat belajar Pendidikan Islam pada siswa kelas VII di MTs Al Muttaqin. Pendekatan yang digunakan adalah kuantitatif dengan metode korelasional. Populasi penelitian adalah seluruh siswa kelas VII, sedangkan sampel diambil dengan teknik simple random sampling. Data dikumpulkan melalui angket tertutup skala Likert yang mengukur intensitas penggunaan media audio-visual dan minat belajar Pendidikan Islam, kemudian dianalisis menggunakan korelasi Product Moment Pearson. Hasil penelitian menunjukkan adanya hubungan positif dan signifikan antara intensitas penggunaan media audio-visual dengan minat belajar Pendidikan Islam siswa. Semakin tinggi intensitas penggunaan media audio-visual yang relevan dan menarik, semakin tinggi pula minat siswa dalam mengikuti pembelajaran Pendidikan Islam. Kata Kunci: Media Audio Visual, Minat Belajar, Pendidikan Islam, Studi Korelasi, Siswa Abstract This study is motivated by the relatively low student interest in learning Islamic Education, despite increasingly adequate learning facilities, including audio-visual media, at school. The research aims to determine the relationship between the intensity of audio-visual media use and students’ interest in learning Islamic Education among seventh-grade students at MTs Al Muttaqin. A quantitative approach with a correlational design was employed. The population comprised all seventh-grade students, and the sample was selected using simple random sampling. Data were collected through a closed-ended Likert-scale questionnaire measuring the intensity of audio-visual media use and interest in Islamic Education learning, and then analyzed using Pearson Product Moment correlation. The findings indicate a positive and significant relationship between the intensity of audio-visual media use and students’ interest in learning Islamic Education. The higher the intensity of relevant and engaging audio-visual media use, the higher the students’ interest in participating in Islamic Education classes. Keywords: Audio-Visual Media, Learning Interest, Islamic Education, Correlational Study, Student.